Sexuality beyond Chastity: Negotiating Gender Intimacy and Sexuality within Roman Catholic Religious Communities in Poland - Jewdokimow, Marcin (Religions, 2022)
In late modernity both religion and sexuality are being elaborated in terms of reflexivity. In this article, we present findings from our research on the topic of constructions of gender, intimacy and sexuality by sisters and brothers in Catholic monasteries in Poland. The findings are based on the mixed-method transformative connection between qualitative (n = 92) and representative sample quantitative research (n = 1543) conducted in 2020. We studied reflexivity on gender, intimacy and sexuality within Catholic religious communities in Poland in order to understand how gender, intimacy and sexuality are presented in the institutionalized framework of religious life. Our study demonstrates that reflexivity on gender, intimacy and sexuality is highly institutionalised and deeply privatized within Catholic religious communities. The article shows that reflexivity of consecrated persons in Poland on gender, intimacy and sexuality is strongly shaped by religious norms (chastity) and subordinated to their religious roles.